Building Independent Villages through Collaborative Governance by Village-Owned Enterprises (Best Practice from Panggungharjo Village, Central Java, Indonesia) - Sri Juni Woro Astuti; Falih Suaedi (Indonesian Association for Public Administration (IAPA), 2018)
This study aims to develop a collaborative governance model applied by village-owned enterprises called